Mapping Village Potential to Tourism Village in Tungu Village, Aru Islands Sub-District - Temalagi, Selva; Kalorbobir, Yohana Magdalena (Jurnal Pengabdian Masyarakat, 2024)
Purpose: This study aims to explore and map the untapped potential of Tungu Village, a coastal area with resources like marine products, waterfalls, Mairang Island, and mangrove forests. The goal is to highlight how these assets can be developed to boost the local economy and turn the village into a unique tourist destination. Method: The project involves mapping Tungu’s tourism and economic potential, focusing on marine tourism, mangrove education tours, and cultural heritage. Data will be gathered through site visits and community discussions to identify key resources and development opportunities. Practical Applications: The mapping will guide village authorities in increasing income through marine tourism, seafood processing, educational tours, and cultural tourism. Developing these areas offers sustainable growth and new revenue streams for the community. Conclusion: The study provides a plan for unlocking Tungu Village's potential, offering a pathway to economic development through tourism and local resources. Success will require collaboration between the village, local government, and community members.